2017
DOI: 10.18203/2349-2902.isj20173205
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of firearm injuries managed at rural tertiary centre in Western Uttar Pradesh, North India

Abstract: Background: Firearm injuries are associated with substantial emotional, physical and financial burden on community and hospital resources leads to profound morbidity. It is a global public health problem and pose therapeutic challenges to surgeons. Proper management of firearm wounds requires a working knowledge of physical factors involved in the creation of such injuries. Regional variations of the parameters of medico legal aspects of firearm injuries are still lacking. Objective is to analyse pattern of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 8 publications
5
9
0
Order By: Relevance
“…In contrast, studies by Singh et al . [ 5 ] from India and Norton et al . [ 28 ] from UK, reported homicidal assault as the main motive behind gunshot injuries in their studies.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In contrast, studies by Singh et al . [ 5 ] from India and Norton et al . [ 28 ] from UK, reported homicidal assault as the main motive behind gunshot injuries in their studies.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, the most affected persons (68%) were between ages 20 and 39 years. This finding is similar to what has been reported in several previous studies although percentages vary from study to study [ 5 , 16 , 18 , 22 , 23 , 26 , 29 , 30 ]. Government at all levels and all stake holders must therefore, make concerted efforts to reduce the incidence of GSI and mitigate its adverse effect on economic productivity and other economic and health indices.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…T his was in agreement with Jorgenson et al 9 in Oklahoma, who found that the most common cases is males (95%) between the ages of 20 and 39 (64%), Singh et al 10 in Uttar, who report ed Males (83.7%).…”
Section: Resultssupporting
confidence: 86%